Too Many Munnies, too Many Americas: the Answer to the Academic Frontier in Clint Eastwood’s Unforgiven - Daniel Candel Bormann (European Journal of American Studies)
Taking William Munny and Clint Eastwood’s Unforgiven as short-hand for America, the present article solves what is probably ‘the’ critical impasse in Unforgiven studies: the degree of complexity of William Munny, and his ascription to the natural or supernatural realm. The article makes the natural interpretation academically binding, and makes a case for complexity in simplicity. To do so, it first makes conscious, and then relocates, critics’ unreflective use of an Aristotelian distinction in their interpretation of English Bob, Little Bill, and William Munny. This relocation allows crucial parallelisms to surface between English Bob and Little Bill, which in turn explain why these characters have to fail as objects of myth. The article then teases out a natural interpretation of William Munny by re-interpreting both Munny’s meeting with Beauchamp and his final dialogue with Little Bill, and explains why this natural allegiance differs from previous natural interpretations of Munny.